Concentration and ecological risk of heavy metal in street dusts of Eslamshahr, Iran. Issue 4 (19th May 2018) - Kamani, Hossein; Mirzaei, Nezam; Ghaderpoori, Mansour; Bazrafshan, Edris; Rezaei, Soheila; Mahvi, Amir Hossein
ABSTRACT: This study was done to evaluate heavy metal concentrations in street dust samples, to compare measured concentrations in samples to background concentrations in order to make evaluations for pollution indices, and to describe the quality of street dust in the studied area in relation to pollution. A total of 30 cumulative samples were collected from the streets of Eslamshahr City. Concentrations of heavy metals were determined using an Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES). Results determined mean concentrations (mg/kg) of the heavy metals Cd, Cr, Cu, Ni, Pb, and Zn, in collected samples of street dust as 0.34, 35.1, 239, 42.4, 71.3, and 573, respectively. I geo values for Cd and Cr, Cu, Ni, Pb, and Zn showed level of moderately polluted, unpolluted, moderately to strongly polluted, unpolluted, moderately polluted and moderately to strongly polluted, respectively. The pattern of total metal concentrations in the studied area was ranked as follows: Zn and Cu>Pb>Cd>Ni>Cr. The highest values for the monomial potential ecological risk ( Er ) were observed for Cd (114). The mean level of RI for the studied soil samples was 192 (91.3–244), which is classed as presenting a strong potential ecological risk.